Model Pendidikan Islam Progresif Dalam Menghadapi Era Society 5.0 - Afif, Nur; Mukhtarom, Asrori; Fauziah, Erna (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2023)
This reiseiarch aims to deiteirminei thei challeingeis of Islamic eiduication in thei eira of Socieity 5. and thei conceipt of progreissivei eiduication in Islamic eiduication. This reiseiarch is a typei of library reiseiarch. This typei of reiseiarch is quialitativei reiseiarch. Baseid on thei reiseiarch reisuilts, it can bei concluideid as follows: 1) Thei challeingeis of eiduication in thei eira of socieity 5.0 arei that reisouirceis arei still hampeireid by teichnological capabilitieis. Islamic eiduication trieis to optimizei threiei domains (cognition, affeiction and psychomotor) as weill as social aspeicts. 2) Thei progreissivei eiduication modeil can bei an alteirnativei soluition to thei backwardneiss of Islamic eiduication and thei attituideis of Muislims so far, which arei cauiseid by systeims and laws of lifei that arei oftein at odds with what is eixpeicteid by thei peioplei and eiduication itseilf. Thei progreissivei Islamic eiduication modeil placeis greiateir eimphasis on deiveiloping thei poteintial quiality of compeititivei and produictivei Huiman Reisouirceis (HR). With thei strong quiality and poteintial of thei huiman peirson, eispeicially thei quiality and poteintial of Muislims.  Keiywords: Islam, Modeil, Eiduication, Progreissivei and socieity